Consumer Readiness for Metaverse Marketing: Evidence from Generations Y and Z in the Philippines - Villarosa, Paula Mae E.; Flora, Angelie Mae D.; Sabordo, Hazel Duds M.; Sotto, Andrea Elizabeth; Torres, Alexi M.; Dio, Eric Arthur N. (International Review of Management and Marketing, 2026)
The emergence of immersive digital environments has created new opportunities for organizations to engage consumers through Metaverse marketing. This study examines the awareness and acceptability of Metaverse marketing among Generations Y and Z in the Philippines. Guided by the Technology Acceptance Model (TAM), awareness was operationalized through the marketing mix dimensions (product, price, place, promotion), while acceptability was measured through perceived usefulness, perceived ease of use, and likelihood of adoption. A descriptive–correlational design was employed using survey data collected from 386 participants in the Philippine cities of Bacolod, Silay, and Talisay. Results indicate substantial awareness and generally positive perceptions of Metaverse marketing among both generational groups. Independent samples t‑tests revealed no significant generational differences in overall awareness or acceptability. Pearson correlation analysis revealed a strong positive relationship between awareness and acceptability (r = 0.746, p < .05). The findings suggest that increasing consumer awareness of immersive digital environments can enhance readiness to adopt Metaverse marketing platforms.